The Job Gap, the Money Gap, and the Responsibility of Legal Educators - Deborah Jones Merritt (Washington University Journal of Law & Policy, 2013)
Today’s law school graduates face a grim prospect: more than half of them will not make a career practicing law. Some of those graduates will enjoy jobs in fields allied with law, but many will settle for work with little connection to the degree they earned. Many of the graduates who land lawyer jobs, meanwhile, will struggle with other limits: stagnant salaries, contingent work, and few promotions. Some number of graduates, the ones who win the legal employment lottery, will build satisfying, remunerative careers as lawyers; there is still good work to be done in law. But the percentage of graduates in the last category is declining, and there is no credible evidence that this market reality will change. Today’s graduates are also paying considerably more for their legal education than graduates did ten, twenty, or thirty years ago. During the last decade alone, law school tuition jumped 67.8 percent at private schools and 151.2 percent at public ones. Over the same ten years, consumer prices rose just 28.1 percent. Law school tuition, in other words, has risen 2.4 to 5.4 times as fast as inflation. At the same time, the median starting salary for law school graduates has declined. Data from two different sources confirm that today’s average graduate earns less, in inflation-adjusted dollars, than graduates did ten or twenty years ago. These trends generate two gaps. The first is between the number of students earning law degrees and the number of lawyering jobs available to them. The second is between the tuition that students pay and the early-career salaries they receive—if they are fortunate enough to find lawyering work. I explore these two shortfalls, the job gap and the money gap, in the first and second sections of this Essay. In the final section, I turn to an equally troubling lacuna: the failure of law schools to acknowledge the harms their graduates are suffering. This responsibility gap is one that we, as educators, have the power to bridge. As I explore the shortfall between our schools’ actions and our responsibilities, I offer several concrete steps to close that gap.
Keywords: legal education; job gap; money gap; National Association for Law Placement; legal services; new lawyers; law schools